Porous polymer electrolyte, preparation method, lithium battery and application
By using in-situ polymerization process in lithium batteries to form porous polymer electrolytes with micro-nano-grade porous structures, the problem of poor processability of porous materials is solved, the solvated structure is controlled throughout the region, and the performance and cycle life of lithium metal batteries are improved.
Patent Information
- Application Number
- CN202411882300.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, porous materials have poor processability and usually need to be coated on the front end of the lithium metal or the side of the separator, which cannot effectively regulate the solvated structure of the global electrolyte, resulting in poor performance of lithium metal batteries.
By adopting an in-situ polymerization process in lithium batteries, polymer monomers with multiple double bonds are mixed with carbonate electrolytes to form a porous polymer electrolyte with a micro-nano-grade porous structure, the solvated structure of the electrolyte is converted from SSIP to CIP, and a solid electrolyte interface rich in LiF is formed.
It realizes the ability to regulate the solvated structure in the entire region, improves the Coulomb efficiency and cycle stability of lithium metal batteries, extends the cycle life of the battery, and is suitable for a variety of lithium battery materials.
Smart Images

Figure CN119890428A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a porous polymer electrolyte and a preparation method thereof, a lithium metal battery and applications thereof. Background Art
[0002] This section is intended to provide background or context for the embodiments of the invention set forth in the claims. The descriptions herein may include concepts that may be explored, but not necessarily concepts that have been previously thought of or explored. Therefore, unless otherwise noted herein, the content described in this section is not prior art with respect to the specification and claims of this application, and is not admitted to be prior art by inclusion in this section.
[0003] Lithium metal (Li) has a very high theoretical specific capacity (3860 mAh g -1 ) and the lowest electrochemical potential (-3.04 V vs. SHE) are considered the "holy grail" of high energy density lithium battery anode materials. However, its incompatibility with traditional electrolytes (such as carbonates) and the growth of dendrites during lithium plating lead to continuous capacity loss, ultimately resulting in low Coulombic efficiency and short-circuit failure. To address this issue, people have extensively explored ways to change the solvation structure of the electrolyte to form inorganic-rich solid electrolyte interfaces (SEIs) to stabilize the electrodes and improve the performance of lithium metal batteries (LMBs).
[0004] Over the past few decades, researchers have mainly achieved the above goals by designing electrolyte strategies, such as highly concentrated electrolytes (HCEs), locally highly concentrated electrolytes (LHCEs), and weakly solvated electrolytes (WSEs), aiming to transform the Li+ solvation structure from solvent-separated ion pairs (SSIPs) to contact ion pairs (CIPs) and cation-anion aggregates (AGGs), thereby promoting the formation of strong inorganic SEIs. Despite these advances, their commercialization is still limited by many challenges, such as the high cost of lithium salts, insufficient wettability in HCEs, the toxicity and cost of fluorinated diluents in LHCEs, and the limited dissociation ability of lithium salts in WSEs.
[0005] Porous materials with nanoscale pores (1-2nm) have attracted attention due to their ability to regulate the solvation structure of the electrolyte without changing the intrinsic properties of the electrolyte. Although porous materials are promising, they are usually processed into thin films (several microns to ten microns thick) and placed at the lithium metal front to regulate the local solvation structure of the electrode / electrolyte interface. However, this regulation ability is limited in distance and cannot regulate the solvation structure of the electrolyte when used in commercial electrodes (≥50μm) with high active material loading. This method of processing porous materials into thin films limits their effectiveness in controlling the global (full area of the cathode-electrolyte-anode) electrolyte solvation structure.
[0006] Therefore, the porous materials in the prior art have poor processability and usually need to be coated on the front end of the lithium metal or one side of the diaphragm and can only regulate the local solvation structure problem of the interface. Summary of the invention
[0007] In order to solve the problem that porous materials in the prior art have poor processability and usually need to be coated on the front end of lithium metal or one side of the diaphragm but can only regulate the local solvation structure of the interface, the purpose of the present invention is to provide a porous polymer electrolyte and a preparation method, a lithium metal battery and its application.
[0008] To solve the above technical problems, in a first aspect, according to some embodiments, the present invention provides a method for preparing a porous polymer electrolyte, comprising:
[0009] Dissolving an electrolyte lithium salt in a carbonate compound solvent in proportion, stirring evenly to obtain a uniform electrolyte solution, wherein the ratio of the electrolyte lithium salt to the carbonate compound solvent is a lithium salt concentration not higher than 5 mol / L;
[0010] Adding polymer monomer molecules containing multiple double bonds into the uniform electrolyte in proportion to obtain a uniform solution, wherein the mass ratio of the polymer monomer ratio is not higher than 20%;
[0011] Adding a thermal initiator to the uniform solution in proportion and stirring the mixture to obtain a transparent solution, wherein the proportion of the thermal initiator is not higher than 2% by weight;
[0012] The transparent solution is used as a precursor solution in the injection step of the soft-pack battery process, a certain amount is added to the soft-pack dry battery, and is allowed to stand at a temperature of 40°C-100°C for 2 hours-20 hours. A porous polymer electrolyte with a full-area solvation structure is obtained through an in-situ polymerization process, and the obtained porous polymer electrolyte framework has pores less than 2nm, wherein the injection amount in the battery is not higher than 4g / Ah.
[0013] Optionally, in some embodiments, the electrolyte lithium salt is one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium nitrate (LiNO3), lithium tetrafluoroborate (LiBF4) and lithium difluorooxalatoborate (LiDFOB).
[0014] Optionally, in some embodiments, the carbonate compound solvent is one or more of ethylene carbonate (EC), diethyl carbonate (DEC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and fluoroethylene carbonate (FEC).
[0015] Optionally, in some embodiments, specifically, the ratio of the electrolyte lithium salt to the carbonate compound solvent is 0.5 mol / L-4 mol / L, and the lithium salt concentration is dissolved in the carbonate compound solvent.
[0016] Optionally, in some embodiments, the polymer monomer with multiple double bonds is one or more of pentaerythritol triacrylate (PETA), pentaerythritol tetraacrylate (PETEA), and pentaerythritol triallyl ether (APE).
[0017] Optionally, in some embodiments, specifically, the mass ratio of the polymer monomer ratio is 4%-15%.
[0018] Optionally, in some embodiments, the thermal initiator is one or more of azobisisobutyronitrile, 2,2'-bisazo-(2,4-dimethylvaleronitrile); and / or,
[0019] Specifically, the amount of liquid injected into the battery cell is 1g / Ah-3g / Ah.
[0020] In a second aspect, an embodiment of the present invention further provides a porous polymer electrolyte prepared by the method of the first aspect.
[0021] In a third aspect, an embodiment of the present invention further provides a lithium battery, wherein the lithium battery is a lithium ion battery or a lithium metal battery, the battery comprises a positive electrode sheet and a negative electrode sheet, and the porous polymer electrolyte described in the second aspect is arranged between the positive electrode sheet and the negative electrode sheet.
[0022] In a fourth aspect, an embodiment of the present invention further provides an application of a porous polymer electrolyte prepared by the preparation method described in any one of the first aspects above in a lithium-ion battery, or an application of a lithium metal battery described in the third aspect above in the field of power batteries, energy storage batteries or 3C batteries.
[0023] The above-mentioned technical scheme of the present invention has at least the following beneficial technical effects: the purpose of the present invention is to provide a porous polymer electrolyte and its preparation method, a lithium metal battery and its application, which can be understood as a porous polymer electrolyte with the ability to regulate the solvation structure in the entire region and its preparation method, as well as a lithium metal battery and a lithium ion battery. The porous polymer electrolyte proposed in the present invention has intrinsic safety characteristics such as no leakage and high thermal stability. The full-region solvation structure regulation method is achieved by combining a porous polymer framework with a commercial carbonate electrolyte. The present invention selects at least one of acrylate and propyl ether with multiple double bonds as a polymer monomer, and after mixing with a carbonate electrolyte, in-situ polymerization is carried out inside a battery. The polymer monomer with multiple double bonds spontaneously undergoes phase separation under the action of a thermal initiator to produce a micro-nano graded porous polymer framework to regulate the solvation structure of the electrolyte uniformly filled therein, from solvent-separated ion pairs (SSIPs) to contact ion pairs (CIPs), and finally produces a solid electrolyte interface (SEI) rich in lithium fluoride (LiF); on the other hand, the hierarchical porous structure enhances the axial permeation channel, ensures the uniformity of the lithium ion flux during the migration process, thereby achieving highly uniform and dense lithium deposition, and finally achieving high coulombic efficiency and stable cycle of lithium metal batteries. At the same time, the solvation structure of CIP can alleviate the graphite layer peeling of the graphite negative electrode during the cycle process, and finally achieve the long cycle life of the graphite-based lithium-ion battery. The present invention adopts an in-situ polymerization process to convert the acrylate and propyl ether monomers with multiple side chains into a polymer framework with micro-nano hierarchical pores in the entire area inside the battery. The synthesized porous polymer framework has a micro-nano hierarchical pore structure, and the electrolyte is evenly filled therein. Since the nanopores of the porous polymer framework and the functional group structure of the side chain can globally regulate the solvation structure of the electrolyte filled therein, and finally form a LiF-rich SEI, it can solve the problem that the porous material in the prior art has poor processability and usually needs to be coated on the front end of the lithium metal or one side of the diaphragm, but can only regulate the local solvation structure of the interface. The present invention adopts an in-situ polymerization process to convert the acrylate and propyl ether monomers with multiple side chains into a polymer framework with micro-nano hierarchical pores in the entire area inside the battery. The synthesized porous polymer framework has pores less than 2nm, and the electrolyte is evenly filled therein. Since the nanopores of the porous polymer framework and the functional group structure of the side chain can globally regulate the solvation structure of the electrolyte filled therein and ultimately form a LiF-rich SEI, the synthesized porous polymer framework has a micro-nano hierarchical pore structure.It can solve the problem that the porous materials in the prior art have poor processability and usually need to be coated on the front end of the lithium metal or one side of the diaphragm, but can only regulate the local solvation structure of the interface. The porous polymer electrolyte proposed in the present invention has the characteristics of regulating the solvation structure in the whole area, and can regulate the solvation structure in the porous polymer framework from SSIP to CIP. After the porous polymer electrolyte proposed in the present invention converts the SSIP solvation structure into CIP, the solvent molecules around the lithium ions are reduced and the anions are increased, which will eventually lead to a significant reduction in the organic components of the SEI formed on the surface of the negative electrode active material, while the inorganic components, especially LiF, are greatly increased. The porous polymer electrolyte proposed in the present invention can increase the number of lithium ion migration and broaden the electrochemical stability window of the electrolyte after regulating the solvation structure. The porous polymer electrolyte proposed in the present invention is rich in micro / nano graded porous structures, which can increase the lateral migration channel, so that the lateral migration flux of lithium ions is increased to regulate the uniform deposition of lithium. The CIP solvation structure obtained by the porous polymer electrolyte proposed in the present invention can reduce the embedding and extraction of solvent molecules in the graphite layer during the battery cycle, so as to achieve high coulomb efficiency and long cycle life of graphite. The porous polymer electrolyte proposed in the present invention can be adapted to conventional positive electrode materials such as ternary (NCM811), lithium cobalt oxide, lithium iron phosphate, etc., and can also be adapted to negative electrode materials such as graphite, silicon carbon and metallic lithium, and can achieve stable circulation of high energy density lithium metal batteries with low lithium negative electrode dosage, providing new ideas and solutions for the practical application of lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the conventional technology, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 This is a digital picture of the porous polymer electrolyte in Example 1 of the present invention;
[0026] Figure 2 is a scanning electron microscope (SEM) image of the porous polymer electrolyte in Example 1 of the present invention;
[0027] Figure 3 This is a transmission electron microscope (TEM) image of the porous polymer electrolyte in Example 1 of the present invention;
[0028] Figure 4 is a pore size distribution diagram of the porous polymer electrolyte in Example 1 of the present invention;
[0029] Figure 5The Raman spectra of the porous polymer electrolyte and the liquid electrolyte in Example 1 of the present invention;
[0030] Figure 6 This is a TEM image of SEI on the surface of lithium metal after cycling of a lithium metal battery assembled with a porous polymer electrolyte in Example 1 of the present invention;
[0031] Figure 7 This is a SEM image of lithium deposition after cycling of a metal lithium battery assembled with a porous polymer electrolyte and a liquid electrolyte in Example 1 of the present invention.
[0032] Figure 8 The cycle performance curve of the metal lithium battery assembled with the porous polymer electrolyte and the liquid electrolyte in Example 1 of the present invention;
[0033] Fig. 9 The SEM images of the graphite particles in the graphite pole piece after the porous polymer is in situ polymerized in Example 2 of the present invention and then cut by a focused ion beam at room temperature and under freezing conditions;
[0034] Fig.10 TEM image of SEI on the graphite surface of the graphite-based lithium-ion battery assembled with a porous polymer electrolyte and a liquid electrolyte after cycling in Example 2 of the present invention;
[0035] Fig.11 The cycle performance curve of the graphite-based lithium-ion button battery assembled with the porous polymer electrolyte and the liquid electrolyte in Example 2 of the present invention;
[0036] Fig.12 The cycle performance curve of the graphite-based lithium-ion soft-pack battery assembled with the porous polymer electrolyte in Example 2 of the present invention;
[0037] Fig.13 This is a digital picture of the porous polymer electrolyte in Example 3 of the present invention;
[0038] Fig.14 is a SEM picture of the porous polymer electrolyte in Example 3 of the present invention;
[0039] Fig.15 This is a pore size distribution diagram of the porous polymer electrolyte in Example 3 of the present invention. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Based on the information contained in this application, it is easy for those skilled in the art to make various changes to the precise description of the present invention without departing from the spirit and scope of the appended claims. It should be understood that the scope of the present invention is not limited to the defined process, properties or components, because these embodiments and other descriptions are only for illustrating specific aspects of the present invention. In fact, various changes that the technicians in this field or related fields can obviously make to the embodiments of the present invention are all covered within the scope of the appended claims.
[0042] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers used in this application to express the amount, percentage, and other numerical values should be understood as modified by the word "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the specification and the appended claims are approximate values, which may be changed according to the different ideal properties attempted to be obtained. Each numerical parameter should at least be regarded as obtained based on the reported significant figures and by conventional rounding methods.
[0043] The starting materials used in the following examples, unless otherwise specified, can be considered to be purchased from commercial sources.
[0044] The purpose of the present invention is to provide a porous polymer electrolyte and a preparation method, a lithium metal battery and an application, which can be understood as a porous polymer electrolyte with the ability to fully regulate the solvation structure and its preparation method, as well as a lithium metal battery and a lithium ion battery.
[0045] The specific implementation method of the present invention comprises the following steps:
[0046] Dissolving an electrolyte lithium salt in a carbonate compound solvent in proportion, stirring evenly to obtain a uniform electrolyte solution, wherein the ratio of the electrolyte lithium salt to the carbonate compound solvent is a lithium salt concentration not higher than 5 mol / L;
[0047] Adding polymer monomer molecules containing multiple double bonds into the uniform electrolyte in proportion to obtain a uniform solution, wherein the mass ratio of the polymer monomer ratio is not higher than 20%;
[0048] Adding a thermal initiator to the uniform solution in proportion and stirring the mixture to obtain a transparent solution, wherein the proportion of the thermal initiator is not higher than 2% by weight;
[0049] The transparent solution is used as a precursor solution in the injection step of the soft-pack battery process, a certain amount is added to the soft-pack dry battery, and is allowed to stand at a temperature of 40°C-100°C for 2 hours-20 hours. A porous polymer electrolyte with a full-area solvation structure is obtained through an in-situ polymerization process, and the obtained porous polymer electrolyte framework has pores less than 2nm, wherein the injection amount in the battery is not higher than 4g / Ah.
[0050] The specific instructions are as follows.
[0051] (1) dissolving lithium salt in a solvent in proportion and stirring to obtain a uniform electrolyte;
[0052] Specifically, the lithium salt described in step (1) is one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium nitrate (LiNO3), lithium tetrafluoroborate (LiBF4) and lithium difluorooxalatoborate (LiDFOB).
[0053] Specifically, the solvent described in step (1) is one or more of ethylene carbonate (EC), diethyl carbonate (DEC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), fluoroethylene carbonate (FEC), etc.
[0054] Specifically, the ratio of lithium salt to solvent in the above step is 0.5 mol / L-4 mol / L of lithium salt dissolved in the solvent, preferably 0.8 mol / L-1.2 mol / L of lithium salt.
[0055] (2) adding the polymer monomer in a certain proportion to the electrolyte obtained in step (1) and stirring to obtain a uniform solution;
[0056] Specifically, the polymer monomer in step (2) is one or more of pentaerythritol triacrylate (PETA), pentaerythritol tetraacrylate (PETEA), pentaerythritol triallyl ether (APE), etc.
[0057] Specifically, the polymer monomer added to the electrolyte in step (2) has a mass ratio of 4% to 15%, preferably 6% to 8%.
[0058] (3) adding a thermal initiator to the solution obtained in step (2) in a certain proportion, and stirring again until a transparent solution is obtained;
[0059] Specifically, the thermal initiator in step (3) is one or more of azobisisobutyronitrile, 2,2'-disazo-(2,4-dimethylvaleronitrile), etc.;
[0060] Specifically, the ratio of the thermal initiator added in step (3) is 0.1% to 1% by weight, preferably 0.5% by weight.
[0061] (4) The transparent solution of step (3) is used as a precursor solution for the injection step in a typical soft-pack battery process, a certain amount is added to the soft-pack dry battery, and the solution is allowed to stand for a period of time at a certain temperature.
[0062] Specifically, the amount of liquid added to the battery cell in step (4) is 1 g / Ah-3 g / Ah, preferably 2 g / Ah-2.5 g / Ah.
[0063] (5) Placing the battery cell injected in step (4) in an oven and heating it for a period of time to obtain a soft-pack battery with a porous polymer electrolyte having a full-area solvation structure by in-situ polymerization.
[0064] Specifically, the oven heating temperature in step (5) is 40°C-100°C, preferably 50°C-65°C; the heating time is 2h-20h, preferably 6h-12h.
[0065] The scheme described in the present invention can be applied to a variety of lithium battery cells, such as: nickel-cobalt-manganese ternary positive electrode||graphite negative electrode, nickel-cobalt-manganese ternary positive electrode||silicon-carbon negative electrode, nickel-cobalt-manganese ternary positive electrode||metal lithium negative electrode, lithium cobaltate positive electrode||graphite negative electrode, lithium cobaltate positive electrode||silicon-carbon negative electrode, lithium cobaltate positive electrode||metal lithium negative electrode, etc.
[0066] The design principle of the present invention is as follows:
[0067] Considering that polymer monomer molecules with three or four double bonds will produce hyper-crosslinking reactions, thereby spontaneously forming porous polymers with nanopores, the electrolyte and polymer monomer molecules containing multiple double bonds are mixed into a precursor, and a porous polymer framework with nanopores is synthesized in the entire area inside the battery cell through an in situ polymerization process.
[0068] Furthermore, the nanopores can spontaneously regulate the solvation structure of the electrolyte, transforming it from SSIP to CIP, and finally obtaining a LiF-rich SEI, thereby regulating the lithium flux and achieving uniform lithium deposition.
[0069] In addition, the solvation structure of CIP can also minimize the exfoliation of graphite layers during battery cycling, ultimately achieving high-performance lithium metal batteries and lithium-ion batteries with long cycles.
[0070] The following is an explanation through specific examples.
[0071] Example 1
[0072] The preparation process of the porous polymer electrolyte and lithium metal soft pack battery of this embodiment is as follows:
[0073] Dissolve LiPF6 with a molar ratio of 1 mol / L in EC and DEC solvents with a volume ratio of 1:1 and stir evenly; then dissolve PETA with a weight percentage of 6 wt% in the above-mentioned electrolyte, stir evenly again, and then add 0.5 wt% AIBN initiator with a weight percentage to dissolve in the above-mentioned solution; inject the solution precursor into the metal lithium soft-pack dry cell at a ratio of 2 g / Ah, and let it stand at 10°C for 24 hours to fully wet the electrode sheet; finally heat and polymerize in a 50°C oven for 6 hours to obtain the final finished metal lithium soft-pack cell, and carry out subsequent testing and characterization. Figure 1 Shown is a digital picture of the porous polymer prepared in this example. Figure 2 The SEM image of the porous polymer framework obtained by in-situ polymerization in the metal lithium battery of this embodiment is shown. Figure 3 Shown is the TEM image of the obtained porous polymer framework. Figure 4 Shown is the pore size distribution curve of the obtained porous polymer framework.
[0074] The above results indicate that the porous polymer electrolyte framework has pores rich in pores smaller than 2 nm, so it can screen the solvent molecules around lithium ions in the electrolyte and only allow lithium ions and anions to pass through. Figure 5 The Raman spectra of the porous polymer electrolyte and the common electrolyte are shown in Figure 1. It can be seen that the solvation structure of the original SSIP is transformed into a solvation structure dominated by CIP under the regulation of the porous polymer framework. Therefore, it is helpful to form an anion-derived LiF-rich SEI. The obtained LiF-rich SEI structure is shown in the cryo-TEM image ( Figure 6 ) confirmed. And because the porous polymer is rich in micro / nano graded porous structure, it can increase the lateral migration channel, so that the lateral migration flux of lithium ions is increased to regulate the uniform deposition of lithium, SEM image ( Figure 7 ) proved that the density of metallic lithium deposited in porous polymer electrolyte is higher than that of lithium deposited in ordinary liquid electrolyte. Thanks to the above-mentioned CIP solvation structure, LiF-rich SEI and uniform lithium deposition, the cycling performance of the porous polymer electrolyte in metallic lithium soft-pack batteries has been greatly improved compared with ordinary electrolytes. Figure 8 The 4.5Ah LiNi with an energy density of up to 455Wh / kg is shown. 0.8 Co 0.1 Mn 0.1 O2(NCM 811)||PPE (porous polymer electrolyte) / LE (liquid electrolyte)||Li soft-pack battery cycle performance comparison. It can be seen from the figure that the capacity retention rate of PPE-based lithium metal soft-pack battery can reach 90.1% after 100 cycles, while the capacity of LE-based lithium metal soft-pack battery declines by 90% after only 20 cycles.
[0075] Example 2
[0076] The preparation process of the porous polymer electrolyte and lithium ion soft pack battery of this embodiment is as follows:
[0077] This embodiment is similar to embodiment 1. LiPF6 with a molar ratio of 1 mol / L is dissolved in EC and DEC solvents with a volume ratio of 1:1 and stirred evenly. Then PETA with a weight percentage of 10 wt% is dissolved in the above-mentioned electrolyte, stirred evenly again, and then 0.5 wt% AIBN initiator is added to the above-mentioned solution. The solution precursor is injected into the NCM at a ratio of 2.5 g / Ah. 811 ||The graphite negative electrode was placed in a soft-pack dry battery cell and allowed to stand at 5°C for 48 hours to fully wet the positive and negative electrode sheets; finally, the mixture was heated and polymerized in a 60°C oven for 12 hours to obtain the final finished lithium-ion soft-pack battery, which was then tested and characterized.
[0078] This example verifies that the porous polymer electrolyte prepared by in-situ polymerization is effective not only in the two-dimensional lithium metal plane, but more importantly, it is also effective in the three-dimensional porous electrode sheet with a thickness of up to 50-100 μm. Fig. 9 The following are SEM images of the graphite pole piece after in-situ polymerization under freezing and room temperature after focused ion beam cutting. It can be seen from the figure that the electrolyte is evenly filled in the porous polymer framework, and they are distributed together in the gaps of the graphite active particles. Fig.10 As shown in the figure, due to the solvation structure of CIP, the porous polymer electrolyte can not only form a LiF-rich SEI on the surface of graphite particles, but also reduce the embedding of solvent molecules in the graphite layer during the cycle because the number of solvent molecules around lithium ions is reduced, thus greatly reducing the degree of exfoliation of the graphite layer. 811 ||PPE||The cycling performance of graphite (Gr) batteries is significantly better than that of NCM 811 ||LE||Gr battery( Fig.11 ), while NCM with an energy density of 263Wh / kg 811 ||PPE||Gr soft pack battery has a cycle life of up to 3000 cycles and the capacity retention rate is still 66.4% ( Fig.12 ).
[0079] Example 3
[0080] The preparation process of the porous polymer electrolyte of this embodiment is as follows:
[0081] Dissolve LiPF6 with a molar ratio of 1 mol / L in EC and DEC solvents with a volume ratio of 1:1 and stir evenly; then dissolve PETEA with a weight percentage of 6 wt% in the above-mentioned electrolyte, stir evenly again, and then add 0.5 wt% AIBN initiator with a weight percentage to the above-mentioned solution; inject the solution precursor into the metal lithium soft-pack dry cell at a ratio of 2 g / Ah, and let it stand at 10°C for 24 hours to fully wet the electrode sheet; finally heat and polymerize in a 50°C oven for 6 hours to obtain the final finished metal lithium soft-pack cell, and carry out subsequent testing and characterization. Fig.13 Shown is a digital picture of the porous polymer prepared in this example. Fig.14 The SEM image of the porous polymer framework obtained by in-situ polymerization in the metal lithium battery of this embodiment is shown. Fig.15 Shown is the pore size distribution curve of the obtained porous polymer framework.
[0082] An embodiment of the present invention further provides a lithium battery, which is a lithium ion battery or a lithium metal battery. The battery includes a positive electrode sheet and a negative electrode sheet, and the porous polymer electrolyte described in the second aspect is arranged between the positive electrode sheet and the negative electrode sheet.
[0083] An embodiment of the present invention also provides an application of a porous polymer electrolyte prepared by the above-mentioned preparation method in a lithium-ion battery, or an application of a lithium metal battery as described in the third aspect in the field of power batteries, energy storage batteries or 3C batteries.
[0084] Obviously, the described embodiments are only some embodiments of the present invention, but not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0085] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the appended claims of the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the appended claims, or the equivalent forms of such scope and boundaries.
Claims
1. A method for preparing a porous polymer electrolyte, characterized in that: include: Dissolving an electrolyte lithium salt in a carbonate compound solvent in proportion, stirring evenly to obtain a uniform electrolyte solution, wherein the ratio of the electrolyte lithium salt to the carbonate compound solvent is a lithium salt concentration not higher than 5 mol / L; Adding polymer monomer molecules containing multiple double bonds into the uniform electrolyte in proportion to obtain a uniform solution, wherein the mass ratio of the polymer monomer ratio is not higher than 20%; Adding a thermal initiator to the uniform solution in proportion and stirring the mixture to obtain a transparent solution, wherein the proportion of the thermal initiator is not higher than 2% by weight; The transparent solution is used as a precursor solution in the injection step of the soft-pack battery process, a certain amount is added to the soft-pack dry battery, and is allowed to stand at a temperature of 40°C-100°C for 2 hours-20 hours. A porous polymer electrolyte with a full-area solvation structure is obtained through an in-situ polymerization process, and the obtained porous polymer electrolyte framework has pores less than 2nm, wherein the injection amount in the battery is not higher than 4g / Ah.
2. The method according to claim 1, characterized in that The electrolyte lithium salt is one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium nitrate (LiNO3), lithium tetrafluoroborate (LiBF4) and lithium difluorooxalatoborate (LiDFOB).
3. The method according to claim 1, characterized in that The carbonate compound solvent is one or more of ethylene carbonate (EC), diethyl carbonate (DEC), vinylene carbonate (VC), vinylethylene carbonate (VEC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and fluoroethylene carbonate (FEC).
4. The method according to claim 1, characterized in that: Specifically, the ratio of the electrolyte lithium salt to the carbonate compound solvent is 0.5 mol / L-4 mol / L, and the lithium salt is dissolved in the carbonate compound solvent.
5. The method according to claim 1, characterized in that The polymer monomer with multiple double bonds is one or more of pentaerythritol triacrylate (PETA), pentaerythritol tetraacrylate (PETEA), and pentaerythritol triallyl ether (APE).
6. The method according to claim 1, characterized in that Specifically, the mass ratio of the polymer monomers is 4%-15%.
7. The method according to claim 1, characterized in that The thermal initiator is one or more of azobisisobutyronitrile and 2,2'-disazo-(2,4-dimethylvaleronitrile); and / or, Specifically, the amount of liquid injected into the battery cell is 1g / Ah-3g / Ah.
8. A porous polymer electrolyte, characterized in that The method is prepared according to claims 1-7.
9. A lithium battery, characterized in that: The lithium battery is a lithium ion battery or a lithium metal battery, and the battery comprises a positive electrode sheet and a negative electrode sheet, and the porous polymer electrolyte as claimed in claim 8 is arranged between the positive electrode sheet and the negative electrode sheet.
10. Use of a porous polymer electrolyte prepared by the preparation method according to any one of claims 1 to 7 in a lithium-ion battery, or use of the lithium metal battery according to claim 9 in the field of power batteries, energy storage batteries or 3C batteries.